The Pandora’s box: Morphological diversity within the genus Amphiglena Claparède, 1864 (Sabellidae, Annelida) in the Mediterranean Sea, with description of nine new species - Giangrande, Adriana; Putignano, Matteo; Licciano, Margherita; Gambi, Maria Cristina (Zootaxa, 2021)
We report the description of nine new taxa of sabellid polychaetes belonging to the genus Amphiglena, of which diversity in the Mediterranean Sea has been widely underestimated. Examined material derived from both new collections along the Italian coast, including four CO2 vents/hydrothermal systems, and from a re-examination of older material previously attributed to A. mediterranera (Leydig, 1851) which was so far the only species of the genus reported for the Mediterranean area. The analysis revealed the presence of different taxa also consistent with a previous molecular analysis conducted on material from the Gulf of Naples and the Salento coast (Ionian Sea). This led to an increase in the number of species in the genus and to highlight the occurrence in the Mediterranean Sea of a high diversity within the genus. A key to the Mediterranean Sea species of Amphiglena is also provided. Some taxa, however, remain for the moment undescribed due to the poor preservation of the old material, and the lack of the type material for this taxon. A major revision of all the Mediterranean material previously attributed to A. mediterranea from both morphological and molecular points of view is needed.